Shoot Development and Non-Destructive Determination of Grapevine (Vitis vinifera L.) Leaf Area - Costanza, P.; Tisseyre, B.; Hunter, J.J.; Deloire, A. (South African Journal of Enology and Viticulture, 2017)
A non-destructive method for determination of grapevine total leaf area is described. It is based on a highly significant correlation found between shoot leaf area and shoot length of Syrah (Vitis vinifera L.). Total leaf area per vine may be determined by using the equations described, by choosing a representative number of primary and secondary shoots and by knowing the total number of shoots of the plant considered. The equation seemed independent of vigour and terroir and reasonably sensitive to changes in leaf area that occurred independent of altered shoot length. It also allowed for recognition of compensation as a result of canopy manipulation. It would therefore be particularly useful for easy comparison of vines in different situations. A significant correlation between leaf fresh and dry mass and leaf area was also found. Dry matter partitioning, investigated to determine the relative importance of the main organs (primary and secondary shoot, leaf, cluster) during the growth period and in relation to primary shoot length, showed that the highest portion of carbon initially accumulated in the leaves, after which the primary shoot had the highest priority, followed by the clusters from veraison to harvest.  Under the conditions of the experiment, secondary shoots and clusters were close in dry mass until veraison, after which berry dry mass increased significantly.